Pakistan - Public Expenditure Management : Accelerated Development of Water Resources and Irrigated Agriculture - World Bank (Washington, DC, 2013)
This report focuses principally on three key dimensions of better public expenditure management in Pakistan. First, it is paramount to continue financial discipline and reduce the overall size of the public sector deficit, including the sizable losses of public enterprises. The modest progress made in reducing the government's fiscal deficit during the past few years has been undermined by the persistence of high level of losses of public enterprises, especially Water and Power Development Authority (WAPDA), and Karachi Electricity Supply Company (KESC). To reduce the unsustainable burden of public debt, the fiscal deficit, which has averaged 5.5 percent of GDP (excluding grants) and 3.4 percent (including grants) during the past three years, must be brought down further. Provision needs to be made for the large and continuing public enterprise losses and unfunded contingent liabilities of the public sector. A strong and successful government revenue mobilization effort, which will gradually raise the ratio of revenues from 17 percent of GDP (FY02) to say 20 percent over the next decade, remains central to restoring Pakistan's fiscal health. But as the experience of the past few years shows, the structural weakness in the taxation structure (relatively heavy dependence on trade taxes) and the institutional weaknesses in the tax collection machinery (especially on the income tax side) will continue to dampen revenue growth for some time. Thus it will be prudent to assume, at best, only moderate growth in the ratio of government revenues to GDP over the next five years. Even on the assumption of a steady increase in the ratio of government revenue to GDP, the growth in overall public spending in real terms will be modest over the next few years because of the need to reduce the deficit further and to fund public enterprise losses and contingent liabilities. Indeed, in the medium term overall public spending as a proportion of GDP is unlikely to increase from the level of 22 percent witnessed in recent years, even if grant assistance remains at a relatively high level.